Effect of stacked breathing exercise on reducing pulmonary infection and complications for patients with pleural effusion - Abd El-Nasser Mohamed, Amal; Anwar Abd El-Aziz, Mervat; Aly Mahgoup, Asmaa; Zareh Hassan, Zain El-abedeen (International Journal of Advanced Nursing Studies, 2021)
Background: Chest expansion exercises are widely used for patients with pleural effusion. One of these exercises is stacked breathing exercise which has shown to be effective in mobilizing greater lung volumes and in achieving and sustaining deep inspiration. But it is not known whether it will have similar effects in patients with pleural effusion and if it has effect on reducing pulmonary infection and complications for these patients.Objective: Was to evaluate the effectiveness of stacked breathing exercise on reducing pulmonary infection and complications for patients with pleural effusion.Design: A randomized controlled experimental study was used in this study.Participants: sixty patients with pleural effusion were selected by convenience sample and randomly assigned into two groups; the intervention and control groups (30 patients each).Method: Three tools were used. Tool I was Pleural effusion assessment tool included demographic and medical history, hemodynamic parameters and assessment of respiratory system. Tool II is stacked breathing exercise tool used to assess the exercise done to the intervention group. Tool III was Patients' outcomes evaluation sheet used to assess the effect of stacked breathing exercise on pulmonary infection score and complications.Results: There were significant differences in pulmonary infection score and complications between the intervention and control groups. Pulmonary infection score in the intervention group was much lower, and their complications were lower than those in the control group.Conclusion: implementing stacked breathing exercise had significant effect in reducing pulmonary infection and complications in patients with pleural effusion than the routine hospital care.Â Â Â